Penggunaan WhatsApp sebagai Media Pencegahan Narkoba bagi Pemuda Medan: Pendekatan Teori Kebutuhan dan Kepuasan - Subuantoro, Dedi; Kholil, Syukur (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This study aims to explore the influence of information needs on youth drug prevention behavior through WhatsApp, using the Uses and Gratification theory. Drug abuse among the youth in Medan is a serious concern, necessitating an effective communication medium to raise awareness and prevention efforts. WhatsApp, as a popular communication application, has great potential in disseminating information related to drug prevention. The research method used is qualitative with a case study approach, where data was collected through interviews and participatory observation. The findings show that youths who feel their information needs are met through WhatsApp tend to be more cautious in their social interactions and more active in sharing information with peers. However, there are challenges in ensuring that all youth understand the content being shared, especially text-based content. The conclusion of this study states that WhatsApp is effective as a communication medium for drug prevention, especially if the content is tailored to the preferences of the youth.